Dry Gangrene in Children with Typhoid Intestinal Perforation: A Report of Two Cases - Lofty-John C. Anyanwu; Aminu M. Mohammad; Lawal B. Abdullahi; Mustapha U. Ibrahim; Aliyu U. Farinyaro; Mohammed S. Aliyu; Stephen K. Obaro (Case Reports in Surgery)
Intestinal perforation is a life-threatening complication of typhoid fever commonly seen in developing countries, but extraintestinal complications are infrequently reported. We report herein two cases of gangrene seen in children managed for typhoid intestinal perforation, highlighting the challenges faced in their management.